The incidence of osteoporosis and vertebral fracture in women with postmenopausal type 2 diabetes mellitus and predisposing factors of vertebral fractures - Kirkizlar, Tugcan Alp; Aktuglu, Mehmet Burak (International Journal of Advances in Medicine, 2021)
Background: Type 2 diabetes mellitus (DM) has an increased fracture risk due to loss of bone quality and tendency to falling. The aim of the study was to analyze the incidence of osteoporosis and vertebral fractures (VF) in postmenopausal women with type 2 DM and to define the risk factors of VF in terms of clinical, metabolic characteristics and diabetes related microvascular complications. Methods: The 42 postmenopausal patients with type 2 DM were included to the study in Haseki Training and Research Hospital outpatient clinics. Results: Osteoporosis with regard to lumbar spine (LS) and femur neck (FN) was 8.4%, 19.4%, respectively. Vertebral fracture ratio was 31%. There was no statistical significance between vertebral fracture and osteoporosis. In logistic regression analysis, longer postmenopausal period, higher postprandial blood glucose (PBG), presence of peripheral neuropathy was found associated with vertebral fracture (p=0.04, 0.04, and 0.05, respectively). Conclusions: In this study we suggest to consider the length of postmenopausal period, PBG and peripheral neuropathy for assessing the risk of VF.